2011
DOI: 10.1080/16070658.2011.11734384
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and obesity

Abstract: The global obesity epidemic continues to gain momentum, and South Africa is one of those countries with an extremely high prevalence of obesity. The reported association between obstructive sleep apnoea (OSA) and obesity has resulted in a parallel increase in the incidence of OSA. Obesity and OSA interact by inducing systemic inflammation, metabolic aberrations and endocrine abnormalities, all of which predispose patients to atherosclerosis and cardiovascular disease. OSA is associated with a pro-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…These include excessive daytime sleepiness, fatigue, morning headaches, memory impairment, an increased tendency to be involved in motor vehicle accidents, personality changes and depression. [4] Obesity is the most powerful risk factor for obstructive sleep apnea OSA. [5] Obesity occurs over time with the consumption of too many calories or too little expenditure of calories through activity or exercise or both overconsumption and underexpenditure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include excessive daytime sleepiness, fatigue, morning headaches, memory impairment, an increased tendency to be involved in motor vehicle accidents, personality changes and depression. [4] Obesity is the most powerful risk factor for obstructive sleep apnea OSA. [5] Obesity occurs over time with the consumption of too many calories or too little expenditure of calories through activity or exercise or both overconsumption and underexpenditure.…”
Section: Introductionmentioning
confidence: 99%
“…This loss of muscle tone leads to a collapse of the upper airway during sleep, especially if a predisposing factor such as obesity is present. [4] STOP-BANG questionnaire is a concise, effective, and reliable OSA screening tool which has a sensitivity of 92.9% and 100%, for detecting moderate and severe OSA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few studies have reported on cytokine changes pre-and post-T&A in obese children. Because TNF-a and IL-6 levels are influenced by OSA and obesity [13,18], to better evaluate the effect of T&A therapy on obese children with OSA and the follow-up risks of EDS, we collected clinical data of AHI, nadir SaO 2 and BMI and determined TNF-a and IL-6 plasma levels before T&A and 6 months after the surgical treatment. Subsequently, we investigated the correlation of TNF-a and IL-6 levels with AHI and BMI measurements and analyzed the likely explanation for the changes pre-and posttreatment.…”
Section: Introductionmentioning
confidence: 99%
“…OSAS is mainly related to obesity, which is defined as a body mass index (BMI) of more than 30 kg/m 2 4. As the prevalence of obesity has increased, there has been a parallel increase in the prevalence of OSAS 5…”
mentioning
confidence: 99%